2022
DOI: 10.1186/s12935-022-02508-y
|View full text |Cite
|
Sign up to set email alerts
|

High PPT1 expression predicts poor clinical outcome and PPT1 inhibitor DC661 enhances sorafenib sensitivity in hepatocellular carcinoma

Abstract: Background Adaptive resistance and side effects of sorafenib treatment result in unsatisfied survival of patients with hepatocellular carcinoma (HCC). Palmitoyl-protein thioesterase 1 (PPT1) plays a critical role in progression of various cancers. However, its role on prognosis and immune infiltrates in HCC remains unclarified. Methods By data mining in the Cancer Genome Atlas databases, the role of PPT1 in HCC were initially investigated. Furtherm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…All three of these genes have previously been linked to cancer. PPT1 can promote tumor growth and has already shown prognostic potential on its own in various cancer and HCC (43,44). Downregulating PPT1 can improve the efficacy of ICIs (45).…”
Section: Discussionmentioning
confidence: 99%
“…All three of these genes have previously been linked to cancer. PPT1 can promote tumor growth and has already shown prognostic potential on its own in various cancer and HCC (43,44). Downregulating PPT1 can improve the efficacy of ICIs (45).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these inhibitors, bafilomycin A1, ROC-325, LS-1-10, BRD1240, cytochalasin E, Lys05, and DC661 can also inhibit autolysosome formation during autophagic process. Bafilomycin A1, ROC-325, LS-1-10, BRD1240, cytochalasin E, Lys05, and DC661 compounds can inhibit autolysosome formation by elevating lysosomal pH ( Yamamoto et al ., 1998 ; McAfee et al ., 2012 ; Aldrich et al ., 2015 ; Carew et al ., 2017 ; Fu et al ., 2017 ; Takanezawa et al ., 2018 ; Zhou et al ., 2020 ; Xu et al ., 2022 ). DC661 is a dimeric CQ derivative ( Xu et al ., 2022 ).…”
Section: Pharmacological Inhibitors Directly Targeting Autophagy Form...mentioning
confidence: 99%
“…Bafilomycin A1, ROC-325, LS-1-10, BRD1240, cytochalasin E, Lys05, and DC661 compounds can inhibit autolysosome formation by elevating lysosomal pH ( Yamamoto et al ., 1998 ; McAfee et al ., 2012 ; Aldrich et al ., 2015 ; Carew et al ., 2017 ; Fu et al ., 2017 ; Takanezawa et al ., 2018 ; Zhou et al ., 2020 ; Xu et al ., 2022 ). DC661 is a dimeric CQ derivative ( Xu et al ., 2022 ). ROC-325, LS-1-10, Lys05, and DC661 have been tested as possible cancer therapeutics in pre-clinical animal models.…”
Section: Pharmacological Inhibitors Directly Targeting Autophagy Form...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Sankey diagram showed that the three srlncRNAs were associated with a few coding genes, including PPT1, PTGDS, and ELOVL1. High PPT1 expression is Frontiers in Genetics frontiersin.org associated with poor prognosis in patients with HCC, and PPT1 inhibition could enhance the sensitivity to sorafenib therapy in HCC (Xu et al, 2022). PTGDs are prognostic biomarkers of breast cancer (Adekeye et al, 2022).…”
Section: Resource Identification Initiativementioning
confidence: 99%